Cellular and Humoral Immune Responses Induced by an HLA Class I–restricted Peptide Cancer Vaccine Targeting WT1 Are Associated With Favorable Clinical Outcomes in Advanced Ovarian Cancer. Issue 1 (8th January 2022) - Nishida, Sumiyuki; Morimoto, Soyoko; Oji, Yusuke; Morita, Satoshi; Shirakata, Toshiaki; Enomoto, Takayuki; Tsuboi, Akihiro; Ueda, Yutaka; Yoshino, Kiyoshi; Shouq, Alzaaqi; Kanegae, Mizuki; Ohno, Satoshi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The HLA-A*24:02–restricted peptide vaccine targeting Wilms' tumor 1 (WT1) (WT1 vaccine) is a promising therapeutic strategy for ovarian cancer; however, its efficacy varies among patients. In this study, we analyzed WT1-specific immune responses in patients with advanced or recurrent ovarian cancer that was refractory to standard chemotherapies and their associations with clinical outcomes. In 25 patients, the WT1 vaccine was administered subcutaneously weekly for 3 months and biweekly thereafter until disease progression or severe adverse events. We assessed Wilms' tumor 1–specific cytotoxic T lymphocytes (WT1-CTLs) and Wilms' tumor 1 peptide-specific immunoglobulin G (WT1235 -IgG). After vaccination, the percentage of tetramer high-avidity population of WT1-CTLs among CD8 + T lymphocytes (%tet-hi WT1-CTL) and the WT1235 -IgG titer increased significantly, although the values were extremely low or below the limit of detection before vaccination (%tet-hi WT1-CTL: 0.003%–0.103%.; WT1235 -IgG: <0.05–0.077 U/mL). Patients who had %tet-hi WT1-CTL of ≥0.25% (n=6) or WT1235 -IgG of ≥0.10 U/mL (n=12) had a significantly longer progression-free survival than those of patients in the other groups. In addition, an increase in WT1235 -IgG corresponded to a significantly longer progression-free survival ( P =0.0496). In patients with systemic inflammation, as evidenced by elevated C-reactive protein levels, the induction of tet-hi WT1-CTL or WT1235 -IgG was insufficient. Decreased serum albumin levels, multiple tumor lesions, poor performance status, and excess ascites negatively influenced the clinical effectiveness of the WT1 vaccine. In conclusion, the WT1 vaccine induced antigen-specific cellular and humoral immunity in patients with refractory ovarian cancer. Both %tet-hi WT1-CTL and WT1235 -IgG levels are prognostic markers for the WT1 vaccine.